Tuning the Thermal Properties of Azopolymers Synthesized by Post‐Functionalization of Poly(propargyl Methacrylate) with Azobenzene Azides: Influence on the Generation of Linear and Circular Birefringences. Issue 21 (8th October 2018) - Roche, Alejandro; García‐Juan, Hugo; Royes, Jorge; Oriol, Luis; Piñol, Milagros; Audia, Biagio; Pagliusi, Pasquale; Provenzano, Clementina; Cipparrone, Gabriella
Abstract: A series of side‐chain polymers with a bifunctional repeating unit are prepared by post‐polymerization functionalization of poly(propargyl methacrylate) (PPMA) with several azides derived from bis(hydroxymethyl)propionic acid (bis‐MPA). The azide incorporates one photoresponsive 4‐cyanoazobenzene unit and one photoinert promesogenic moiety at each repeating unit. Both the effect of the photoinert (4‐cyanobipheynyl vs 4‐cyanotolane) and of the linking group (ester vs carbamate) on the liquid crystalline properties and the generation of optical anisotropy, linear or circular birefringences are explored. Abstract : A flexible approach to bifunctional polymers combining promesogenic and photoresponsive moieties in the same repeating units is described using click chemistry tools. By tuning the linking groups of the bifunctional moieties to the polymethacrylic chain, the liquid crystallinity and the photoinduction of simultaneous linear and circular birefringence is controlled.